Reticulocitos y su relación con anemia ferropénica en niños menores de 2 años procedentes del cantón Alausí 2024. - Espinoza Espinoza, Tanya Aracelly (2025)
The main objective of this research study was to consider reticulocyte values and their relationship with iron deficiency anemia in children under 2 years of age from the canton of Alausí 2024. Immature erythrocytes play an important role as key indicators in the evaluation of various hematological disorders, as their analysis is particularly relevant in the diagnosis and monitoring of anemia, such as that caused by iron deficiency, which mainly affects preschool children, a critical stage in child development. A quantitative, cross-sectional study with a prospective time sequence and a non-experimental field design was carried out, based on the interpretation of data generated according to the results of blood tests. The study population included 248 infants under 2 years of age from the parishes of Alausí Matriz, Totoras, Achupallas, Multitud, Tixán, Sibambe, Guasuntos, Nizag, Sevilla, and Huigra. Using non-probability convenience sampling, a sample of 240 children who met the inclusion criteria for the study was selected. The results obtained allowed us to establish a significant relationship between low erythropoietic activity and iron deficiency anemia, especially in the 6- to 24-month age group, with statistically significant corrected hemoglobin and hematocrit results (p = 0.004 and p <0.001), indicating a microcytic hypochromic regenerative disorder, characteristic of a certified iron deficiency. It was concluded that counting each reticulocyte in conjunction with erythrocyte parameters is useful in assessing the hematological status of children.